Education for Social Development in accordance with the Threefold Training - จันทร์ชนะ, พระมหาอุดร ปญฺญาวฑฺฒโก (Journal of Educational Review Faculty of Education in MCU, 2018)
Society is ill because of the weakness in mentality, emotion, economic, politics, education, culture and environment. That also reflects the image of people in the society confronting with the problems. Education is one of the important issues raised for discussion in the society because it can solve as well as increase social problems. The education management in Buddhism is to train physical, verbal, mental and intellectual domains to achieve three ultimate goals; Sila (Morality), Samadhi (Mentality), and Paññā (Wisdom), called Ti- sikkhā or the Threefold Training. The social development by Sila is to have discipline and follow rules and laws. The mental development by Samadhi is to train the mind to be mindful, strong and thrive with virtue. The intellectual development by Paññā is to know and understand the things as they really are, to realize the changes in the society, the world and life, and to set the mid free from illusions and societal trends.